1997
DOI: 10.1111/j.1460-2695.1997.tb00298.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Ageing at Intermediate Temperatures on the Monotonic Stress‐strain Behaviour and Fracture Toughness of a Duplex Stainless Steel

Abstract: The mechanical behaviour of the duplex stainless steel AISI 329 has been investigated for ageing times up to 15,000 h at 475,425, 375, 325 and 275°C. The study has concentrated on changes in the monotonic stressstrain behaviour and fracture toughness as a function of ageing temperature and time. It is shown that the tensile behaviour of the steel changes strongly due to ageing. A large increase in yield strength and reductions in ductility and fracture toughness are observed. The deformation hardening behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The effect of ageing on fatigue behaviour of duplex stainless steels should be also related to this change in ferrite, which increases the yield strength by a factor as high as 2. At the same time, ageing tends to change the mechanism of fracture from nucleation and growth of ductile voids to cleavage with a strong reduction in fracture toughness (see [ 3 ] ) .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The effect of ageing on fatigue behaviour of duplex stainless steels should be also related to this change in ferrite, which increases the yield strength by a factor as high as 2. At the same time, ageing tends to change the mechanism of fracture from nucleation and growth of ductile voids to cleavage with a strong reduction in fracture toughness (see [ 3 ] ) .…”
Section: Discussionmentioning
confidence: 98%
“…This change makes the steel brittle and limits severely its use in many potential applications. The influence of ageing on the mechanical behaviour under monotonic loading has been the subject of the first part of this work [3].…”
Section: Introductionmentioning
confidence: 99%
“…As previously commented, at this temperature, the kinetics of spinodal decomposition is quite fast and the long duration of the test induces a prominent aging effect. [11,14] Finally, at De t /2 5 9 3 10 À3 , secondary hardening was never observed. The reason is probably that fatigue lives at this high strain amplitude were too short to reach this stage.…”
Section: E Secondary Hardeningmentioning
confidence: 80%
“…At 475°C, the kinetics of spinodal decomposition of ferrite is quite fast. [11,14] It has been proven that this microstructural change interferes with dislocation glide, inhibiting cross-slip, and, as a consequence, high imposed strain values are required to induce plastic activity in aged ferrite. [12,[39][40][41] Llanes et al [12] performed room-temperature tests on DSS that had been previously aged during 25 and 200 hours at 475°C and showed that, at plastic strains around 10 À3 , substructural scenarios were very different for as-received and thermally aged steels.…”
Section: Substructural Features Associated With Cyclic Deformationmentioning
confidence: 99%
See 1 more Smart Citation